Extended and local structural description of a kaolinitic clay, its fired ceramics and intermediates: an XRD and XANES analysis - Andrini, Leandro Rubén (2016)
The thermal transformations processes of kaolinite (K) in kaolinitic clays is knownto consist of a dehydroxylation into metakaolin (MK) at ≈600 °C, followed by the formation of a spinel type aluminosilicate (SAS) at≈980 °C, and finally the development of mullite (M) at higher temperatures (1200–1300 °C). The structural characterization of thesematerials is generally based on X-ray diffraction (XRD) studies,where the XRD features of K and M are well defined due to their crystalline nature, but as consequence of the low crystallinity of MK and SAS, the precise characterization of these phases is not possible using this technique. In this study the nature of aluminum atoms in the different materials obtained by thermal treatments of a kaolinite is investigated using Al K-XANES and compared with other well-known aluminum containing materials. XRD and SEM characterization were also carried out. The results confirm the potentiality of this synchrotron based techniques for the characterization of natural materials and ceramics especially with low crystallinity. Particularly the mullite aluminums Al K-XANES spectra were not reported before.